Development of Web-Based Learning Media with an Inquiry Model to Enhance Learning Outcomes and Student Independence in Elementary Schools - Rosbina, Atania; Wardani, Sri; Haryono, Haryono (Papanda Publisher, 2025)
This study aimed to develop a web-based learning medium utilizing an inquiry model to enhance primary school students' cognitive learning outcomes and learning independence. The development procedure followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 60 fifth-grade elementary school students, divided into experimental and control groups. Data collection techniques included observation, questionnaires, and learning achievement tests. Media validity assessments by material and media experts yielded an average score of 94% (